2018
DOI: 10.1002/jin2.36
|View full text |Cite
|
Sign up to set email alerts
|

Structural variations in hyperbranched polymers prepared via thermal polycondensation of lysine and histidine and their effects on DNA delivery

Abstract: The successful clinical translation of nonviral gene delivery systems has yet to be achieved owing to the biological and technical obstacles to preparing a safe, potent, and costeffective vector. Hyperbranched polymers, compared with other polymers, have emerged as promising candidates to address gene delivery barriers owing to their relatively simple synthesis and ease of modification, which makes them more feasible for scale-up and manufacturing. Here, we compare hyperbranched poly(amino acids) synthesised b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 55 publications
2
19
1
Order By: Relevance
“…The polyplexes were prepared at the N/P ratio of 10, where they showed the best transfection efficiency as reported in our previous work. 28 The size and zeta potential measurements indicated that the polymers efficiently condensed plasmid DNA into positively charged nanoparticles of around 150 nm in diameter and the AFM images confirmed the results (Fig. S1, ESI †).…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…The polyplexes were prepared at the N/P ratio of 10, where they showed the best transfection efficiency as reported in our previous work. 28 The size and zeta potential measurements indicated that the polymers efficiently condensed plasmid DNA into positively charged nanoparticles of around 150 nm in diameter and the AFM images confirmed the results (Fig. S1, ESI †).…”
Section: Resultssupporting
confidence: 75%
“…Hyperbranched polylysine, hyperbranched polylysine-co-histidine, and their FITC-labelled forms were prepared and characterised as described previously. 28 Branched polyethyleneimine (25 kDa), methylthiazolyldiphenyl-tetrazolium bromide (MTT), the annexin V-FITC/PI apoptosis detection kit, N-acetylcysteine (NAC) and all buffers were purchased from Sigma-Aldrich. The Cytotoxicity Detection Kit PLUS (for LDH) was obtained from Roche.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations